The Process of Conceptualization as a Basis for Categorization - Makhammadovna, Mamatova Feruza (International Journal on Integrated Education, 2023)
The article gives explanation how the process of conceptualization could be the principal aspect of categorization of a concept. Language, proceeding from its resources, verbalizes this experience only in part. Many differences in the semantic volumes of concepts are determined by one or another socio-cultural context, and socio-cultural stereotypes become "cognitive guidelines" of the category.